Biochemical and behavioral effects of PDE10A inhibitors: Relationship to target site occupancy. (March 2016) - Li, Yu-Wen; Seager, Matthew A.; Wojcik, Trevor; Heman, Karen; Molski, Thaddeus F.; Fernandes, Alda; Langdon, Shaun; Pendri, Annapurna; Gerritz, Samuel; Tian, Yuan; Hong, Yang; Gallagher, Lizbeth; et al.
Abstract: Phosphodiesterase 10A (PDE10A) inhibitors increase the functionality of striatal medium spiny neurons and produce antipsychotic-like effects in rodents by blocking PDE10A mediated hydrolysis of cAMP and/or cGMP. In the current study, we characterized a radiolabeled PDE10A inhibitor, [ 3 H]BMS-843496, and developed an ex vivo PDE10 binding autoradiographic assay to explore the relationship between PDE10 binding site occupancy and the observed biochemical and behavioral effects of PDE10 inhibitors in mice. [ 3 H]BMS-843496 is a potent PDE10A inhibitor with a binding affinity (KD ) of 0.15 nM and a functional selectivity of >100-fold over other PDE subtypes tested. Specific [ 3 H]BMS-843496 binding sites were dominant in the basal ganglia, especially the striatum, with low to moderate binding in the cortical and hippocampal areas, of the mouse and monkey brain. Systemic administration of PDE10 inhibitors produced a dose- and plasma/brain concentration-dependent increase in PDE10A occupancy measured in the striatum. PDE10A occupancy was positively correlated with striatal pCREB expression levels. PDE10A occupancy was also correlated with antipsychotic-like effects measured using the conditioned avoidance response model; a minimum of ∼40% occupancy was typically required to achieve efficacy. In contrast, a clear relationship between PDE10A occupancy and catalepsy scores, a potential extrapyramidal symptom readout in rodent, was not evident. Highlights: [ 3 H]BMS-843496, a potent and selective PDE10A radioligand, was characterized. Radioligand binding was highest in striatum, subthalamic n. and substantia nigra. PDE10A occupancy correlated with striatal pCREB expression. ≥40% PDE10A occupancy was required to achieve antipsychotic-like effects. Cataleptic effects of PDE10A inhibitors were not consistently related to occupancy.